The ‘Right to Be Forgotten’: An Ethical Dilemma - La Roche, Claire Reeves (Journal of Leadership, Accountability and Ethics, 2020)
Should there be a digital ‘right to be forgotten’? Almost everyone has done something as a teenager or young adult that they later regret. With the advent of the Internet, social media, and the ubiquitous cell phone, a de facto permanent digital record of almost everything that is said or done has been created. These digital records are easily accessible, shared, and may have devastating personal, educational and professional consequences. This paper summarizes the status of the ‘right to be forgotten’ and provides specific incidents to inspire lively debate. The European Union’s ‘right to be forgotten’ law and California’s Minor Erase Law are both outlined. Two cases involving youthful indiscretions, one by a minor and the other by a young adult, are presented. Suggestions are made for discussion questions with additional teaching notes italicized.